PENANAMAN MODAL DALAM PERTUMBUHAN EKONOMI - Sri Purwaningsih (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2021)
Investment is any form of investment activity, either by domestic investors or byforeign investment to carry out business in the territory of the Republic of Indonesia. This study aims to determine the importance of investment in economic growth. The presence of investment can drive the country's economy, in addition to creating a multiplier effect which is expected to increase added value for the government and society. In developing countries, including Indonesia, the inflow of foreign capital is quite profitable if it is actually used for national development, especially to drive the country's economy. Investment facilities are provided with consideration of the foreign power level of the economy and the country's financial condition and are promotive compared to those provided by other countries. The importance of the certainty of this investment facility encourages more detailed regulation of the form of fiscal facilities, land rights facilities, immigration facilities, and import licensing facilities. In conclusion, if a country is to achieve sustainable economic growth, it must have a certain economic structure, that is, it must be able to mobilize all its capital and natural resources capabilities so that it can achieve a productive investment level of 10% of its maximum income